ANALISIS PENDAPATAN ASLI DAERAH (PAD) TERHADAP KEMAMPUAN PEMBIAYAAN KEUANGAN DAERAH KABUPATEN MUSI BANYUASIN - Asoka, Rano (Balance : Jurnal Akuntansi dan Bisnis, 2017)
ABSTRACT This study aimed to determine the ability of local revenue (PAD) to the regional finance of Musi Banyuasin Regency. The object of this research is Musi Banyuasin Regency. Data analysis technique used in this research was qualitative analysis technique. The results of this study indicated that the ratio of finance (Decentralization degree) showed that the ability of the original income of the district government of Musi Banyuasin could be said to be not good / independent. It was because the average comparison between Local Own Revenue (PAD) to the Total Revenue District Government of Musi Banyuasin less than 50%. Effectiveness ratio showed that on average from 2010 to 2014 amounted to 103.23%. This could be said to be effective because with the target set was worth more than 100%. With the realization of local revenues on average by 103.23%, the Local Own Revenue (PAD) of Musi Banyuasin Regency based on the ratio of the effectiveness of local revenue was good enough. The degree of Fiscal Autonomy (DOF) of 4.31% with very less criteria. This means that the tendency of the ability of local government of Musi Banyuasin Regency in self-financing activities of government administration, development and service to the community was still very low. Routine Capability Indicators (IKR) of Musi Banyuasin Regency from 2012 to 2014 were up down, on average Index Routine Capability (IKR) was 4.23% with very less criteria. This indicated that the Government of Musi Banyuasin Regency was dependent on the central government